An Investigation into Credit Risk Management on Non-Performing Loans in Microfinance Institutions. A case of Zimbabwe Microfinance Fund (ZMF) 2017 - 2018 - Chambati, Tafadzwa Simbarashe (Midlands State University, 2020)
The research sought to investigate into credit risk management as a tool to bring down the level of non-performing loans in Microfinance Institutions .A case of Zimbabwe Microfinance Fund (ZMF) .The study is arranged starting with the introduction of the chapter which was followed by the background of the study highlighting factors related to credit risk management and non performing loans. Statement of the problem will show what triggered the researcher to carry out such a research. Finally the conclusion will elaborate on the findings, conclusions made and recommendations that can be adopted to bring down the level of non -performing loans.